An injectable subunit vaccine containing Elongation Factor Tu and Heat Shock Protein 70 partially protects American bison from Mycoplasma bovis infection - Kaplan, Bryan S.; Dassanayake, Rohana P.; Briggs, Robert E.; Kanipe, Carly R.; Boggiatto, Paola M.; Crawford, Lauren S.; Olsen, Steven C.; Menghwar, Harish; Casas, Eduardo; Tatum, Fred M. (Frontiers in Veterinary Science, 2024)
Mycoplasma bovis (M. bovis) is the etiologic agent of high mortality epizootics of chronic respiratory disease in American bison (Bison bison). Despite the severity of the disease, no efficacious commercial vaccines have been licensed for the prevention of M. bovis infection in bison. Elongation Factor Thermal unstable (EFTu) and Heat shock protein 70 (Hsp70, DnaK) are highly conserved, constitutively expressed proteins that have previously been shown to provide protection against M. bovis infection in cattle. To assess the suitability of EFTu and Hsp70 as vaccine antigens in bison, the immune response to and protection conferred by an injectable, adjuvanted subunit vaccine comprised of recombinantly expressed EFTu and Hsp70 was evaluated. Vaccinates developed robust antibody and cellular immune responses against both EFTu and Hsp70 antigens. To assess vaccine efficacy, unvaccinated control and vaccinated bison were experimentally challenged with Bovine Herpes Virus-1 (BHV-1) four days prior to intranasal infection with M. bovis. Vaccinated bison displayed reductions in joint infection, lung bacterial loads, and lung lesions compared to unvaccinated controls. Together, these results showed that this subunit vaccine reduced clinical disease and bacterial dissemination from the lungs in M. bovis challenged bison and support the further development of protein subunit vaccines against M. bovis for use in bison.